TFIID or not TFIID, a continuing transcriptional SAGA. (9th January 2017) - Kubik, Slawomir; Bruzzone, Maria Jessica; Shore, David
Abstract : Eukaryotic protein‐coding genes are typically classified into two groups: those with expression regulated by specific signals versus the relatively constant "housekeeping" genes. Although these differences are associated with alternative modes of RNA polymerase II (RNAP II) pre‐initiation complex (PIC) assembly, a role for gene‐specific activators in controlling "regulatability" has been difficult to rule out. To address this question, de Jonge et al (2017 ) studied a group of genes controlled by a common activator but dependent on either TFIID or SAGA and found that the magnitude of regulation strongly correlates with the mechanism of PIC assembly. Abstract : Alternative modes of transcriptional pre‐initiation complex assembly rather than gene‐specific activators differentiate housekeeping gene expression from regulated gene expression.